Analisa Konsistensi Hukum Dalam Penetapan Isbat Nikah (Studi Kasus Penetapan Nomor 520/pdt.p/2019/pa.lmj): - Hisbulloh Hadziq, Hadziq; Mawahib, Mahdil (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This writing is researching the extent of consistency of judges' decisions in court regarding the legal regulations that stipulate that the submission of a marriage confirmation (isbat nikah) when one party has passed away must be submitted in a contentious manner, meaning that there must be a family member of the deceased party as the opposing or respondent party, and the product of the marriage confirmation is in the form of a judgment, not a determination. However, the case of the marriage confirmation application in the Religious Court of Lumajang Regency, East Java, in case number 520/Pdt.P/2019/PA.Lmj, was granted by the Panel of Judges voluntarily, even though it should have been submitted as a contentious case. This research utilizes the normative juridical research method with a case approach, aiming to understand how legal rules or norms are applied in legal practice. The research findings indicate that the submission of marriage confirmation application number 520/Pdt.P/2019/PA.Lmj was not submitted in a contentious manner but was submitted voluntarily due to a legal issue, namely that the husband's family could not be seated as heirs because all of them are non-Muslims (Hindus) and therefore cannot be categorized as heirs.